2016
DOI: 10.1249/mss.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motor versus Cardiovascular Exercise Training on Children’s Working Memory

Abstract: These findings add to the knowledge base relating different types of exercise and WM. Besides the efficiency of cardiovascular exercise training, a special motor-demanding intervention seems to be a beneficial strategy to improve WM in preadolescent children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
5
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 37 publications
7
134
5
5
Order By: Relevance
“…Furthermore, boys´ brains may be more vulnerable to environmental factors, such as increased adiposity, than that of girls (Isaacs et al 2008). These results together suggest that motor performance may be more important for academic achievement than adiposity in boys and therefore emphasize motor skill training during early and mid-childhood (Haapala, 2013;Koutsandreou, Wegner, Niemann, & Budde, 2016;Robinson et al, 2015). Reasons for these observations on the mediating effects of motor performance are complicated and multifaceted, but may include low levels of physical activity during early childhood that have led to increased adiposity, poor motor performance, and suboptimal development of brain and thereby poor academic achievement (Donnelly et al, 2016;Robinson et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, boys´ brains may be more vulnerable to environmental factors, such as increased adiposity, than that of girls (Isaacs et al 2008). These results together suggest that motor performance may be more important for academic achievement than adiposity in boys and therefore emphasize motor skill training during early and mid-childhood (Haapala, 2013;Koutsandreou, Wegner, Niemann, & Budde, 2016;Robinson et al, 2015). Reasons for these observations on the mediating effects of motor performance are complicated and multifaceted, but may include low levels of physical activity during early childhood that have led to increased adiposity, poor motor performance, and suboptimal development of brain and thereby poor academic achievement (Donnelly et al, 2016;Robinson et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…So, other factors instead of physical exercise must be playing a significant role in this situation. In fact, Koutsandreou et al (2016) showed that low intensity exercises with high cognitive challenge are related to motor control. That means that cognitive interventions or motor learning intervention can also have a large impact on cognitive responses.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 In general, the effects of physical activity intervention on executive function are presumed to be moderated by cognitive engagement and motor control requirements. 21,35,36 For example, a previous randomized control trial compared the effects of a 10-week-long cardiovascular exercise (focused on improvement of cardiovascular fitness through running and running-based games of moderate-to-vigorous intensity) and motor exercise (focused on the improvement of fine and gross motor body coordination through playful balance, bilateral coordination, hand-eye coordination, and leg-arm coordination exercises as well as spatial orientation and reaction to moving objects/persons) program on executive function in children aged 9-10 years. 36 Their results showed that both interventions improved executive function to a greater extent than that in the control group, with a stronger effect in the motor exercise group.…”
Section: Relationship Of Specific Sports Participation To Academic mentioning
confidence: 99%
“…21,35,36 For example, a previous randomized control trial compared the effects of a 10-week-long cardiovascular exercise (focused on improvement of cardiovascular fitness through running and running-based games of moderate-to-vigorous intensity) and motor exercise (focused on the improvement of fine and gross motor body coordination through playful balance, bilateral coordination, hand-eye coordination, and leg-arm coordination exercises as well as spatial orientation and reaction to moving objects/persons) program on executive function in children aged 9-10 years. 36 Their results showed that both interventions improved executive function to a greater extent than that in the control group, with a stronger effect in the motor exercise group. 36 In addition, individual sports are more affected by the participants performance and less dependent on others for competitive achievement, which could partially explain the differences in self-regulation skills between individual sports and team sports.…”
Section: Relationship Of Specific Sports Participation To Academic mentioning
confidence: 99%